OBSERVATIOfJS ON THE DEVELOPMENTAL STAGES OF THE SMOOTH DCiGFISH, ERIDACNIS RADCLIFFEI SMITH FROM GULF OF MANNAR - Nair, R V; Appukkuttan, K K (Indian Journal of Fisheries, 2011)
The structure of mature reproductive organs of fifteien adult females ofEridacn'.s radcliffei. ranging in total length from 150 to 218 mm collected fromthe trawl catches off Mandapam in Gulf of Mannar during February, 1972 at adepth ranging frori 100 to 150 fathoms were studied and the various stages ofintra-uterine embryos are described and discussed. A close examination of differentstages of embryos revealed that this species exhibits ovoviviparous type ofdevelopment. The intra-uterine egg is enclosed in a thin shell membrane whichdisappears when the embryo develops inside the uterus. The embryos are seenfree inside the uterus and no placental connection has been observed in anystage of development.